Perancangan Sistem Informasi Akademik Sekolah Dasar Berbasis Mobile - Heilbert A. Mapaly; Henry V. F. Kainde; Salvius P. Lengkong; Jofrel J. Rembet; Fransiscus X. Senduk (Jurnal Teknik Elektro dan Komputer, 2022)
Abstract — In an increasingly competitive world of Education, many institutions are looking for technology that helps improve performance. Academic information system is a system developed for the purpose of managing academic data by using computer technology and transforming the process of academic activities into useful information. This study aims to develop an Android mobile application to provide academic information more easily. In this research carried out a number of stages such as Literature Study, Data Collection, System Design and Data Model, System Development and Data Processing, Testing and Evaluation, Reporting and Publication. This application's availability is incredibly beneficial for academic administration, particularly when tracking student attendance. This software still needs a lot of work and is in its early stages. Key words—Academic Information System; Android; Elementary School; Software; Abstrak — Dalam dunia Pendidikan yang semakin kompetitif, banyak institusi mencari teknologi yang membantu meningkatkan kinerja. Sistem informasi akademik adalah suatu sistem yang dikembangkan untuk tujuan pengelolaan data akademik dengan menggunakan teknologi komputer dan mengubah proses kegiatan akademik menjadi informasi yang bermanfaat. Penelitian ini bertujuan untuk mengembangkan aplikasi mobile Android untuk memberikan informasi akademik secara lebih mudah. Di dalam penelitian ini dilakukan sejumlah tahapan seperti Studi Pustaka, Pengumpulan Data, Perancangan Sistem dan Model Data, Pembuatan Sistem dan Pengolahan Data, Pengujian dan Evaluasi, Pelaporan dan Publikasi. Adanya aplikasi ini sangat membantu dalam dalam administrasi akademik khususnya dalam melakukan monitoring presensi siswa. Aplikasi ini masih dalam tahap awal dan membutuhkan banyak penyempurnaan. Kata kunci — Android; Sekolah Dasar; Sistem Informasi Akademik; Software;